Near-rational equilibria in heterogeneous-agent models: A verification method - Leonid Kogan; Indrajit Mitra (Federal Reserve Bank of Atlanta, 2021)
We propose a general simulation-based procedure for estimating the quality of approximate policies in heterogeneous-agent equilibrium models, which allows verification that such approximate solutions describe a near-rational equilibrium. Our procedure endows agents with superior knowledge of the future path of the economy, while imposing a suitable penalty for such foresight. The relaxed problem is more tractable than the original, and it results in an upper bound on agents' welfare. Our method is general and straightforward to implement, and it can be used in conjunction with various solution algorithms. We illustrate our approach in two applications: the incomplete-markets model of Krusell and Smith (1998) and the heterogeneous firm model of Khan and Thomas (2008).
Keywords: C86; D52; 330; numerical solutions; accuracy; approximations; simulations